Implementation of Teachers and Parents in Developing Children’s Creativity in Playing Playdough - Hita Astiningrum (HADHANATUNA: Journal of Early Childhood Education, 2025)
This research is based on a phenomenon in Ar Rohman Plosokandang Kindergarten, it was found that there were children who were less interested in being creative using Playdough. The type of research used in this study when viewed from the location of the data source is included in the field research category. Data collection techniques are observation, interviews (interviews), documentation. The data analysis techniques are data reduction, data presentation and drawing conclusions. The results of the research are Playdough game media can stimulate the development and growth of Early Childhood, because the ingredients for making Playdough consist of wheat flour, water, salt, oil and food coloring. Playdough that is made flexible and has many colors will attract children’s attention so that children can learn while playing which can train children’s creativity development. The development of children with Playdough games seen from the results of the percentage of children’s class development achievements shows that children who have the final achievement of developmental start to develop (MB) are 3 children or 17.65% and only 14 children or 82.35% have the final achievement of developmental development according to expectations (BSH).